IoT-based material height monitoring and temperature-humidity control system with ESP32 on a Dosimat Feeder Hopper at PT. Semen Padang - Illahi, Zikri; Mirshad, Emilham (Department of Electrical Engineering Universitas Negeri Padang, 2025)
A hopper is a temporary storage container for rock material before it is fed by a feeder into a crusher. At PT Semen Padang, monitoring of material in the dosimat feeder hopper is still local, limiting supervision flexibility and response time, as well as lacking temperature and humidity control, which can degrade sensitive materials such as gypsum. This study aims to design an integrated system using Internet of Things (IoT) technology to overcome these limitations. The system employs an ESP32 microcontroller as the main processor, using an HC-SR04 ultrasonic sensor to measure material height and two DHT22 sensors to monitor temperature and humidity. Based on sensor readings, the ESP32 controls a DC motor for the filling conveyor and fans for cooling through a relay module. Real-time data visualization is implemented via the Blynk IoT platform for remote monitoring. Testing shows that the HC-SR04 sensor has an accuracy of 95.44%, while the DHT22 sensor achieves 98.62% accuracy. The automatic control system worked correctly according to logical conditions, and the configuration using four fans proved most effective for reducing temperature. Data transmission to Blynk was successful and consistent. In conclusion, the IoT-based monitoring and control system enhances operational efficiency and material quality in industrial settings. It provides a reliable model for implementing remote monitoring and automation, supporting modernization in similar industrial processes through improved supervision, environmental control, and system responsiveness